Integration of Transcriptomics and Metabolomics Provides Insight into the Growth-Promoting Functions of Solanum khasianum Endophyte in Medicago sativa - Jiahui Li; Shijia Zhou; Jiaru Fang; Qihang Cai; Yanbo Yang; Zhenghai Sun; Liping Li; Weiwei Li (Agronomy)
Medicago sativa is an important forage crop; its value is mainly concentrated in its economic aspects. The growth cycle and growth rate of M. sativa have an important influence on its economic benefits. Alternaria alstroemeriae has often been used as a pathogenic bacterium in previous studies, and studies on the growth-promoting effects of A. alstroemeriae are rare. This study aimed to assess the effects of A. alstroemeriae on the growth parameters of M. sativae and to investigate the molecular and metabolic mechanisms of M. sativa. M. sativa showed significant improvement in plant height, root length, fresh weight, and dry weight compared to uninoculated control plants. By integrating the results of transcriptome and metabolome analysis, A. alstroemeriae may promote plant growth by regulating genes associated with the biosynthetic pathways of flavonoids, anthocyanins, and proanthocyanidins in plants. These research findings provide a theoretical basis for future verification of the molecular response mechanisms and metabolic regulation of A. alstroemeriae-promoted plant growth. This study also provides a theoretical basis for sustainable agricultural development.